Investigation of critical response characteristics of micro-droplets under the action of low-frequency acoustic waves - Bai, Wenwen; Shi, Yang; Zhao, Zhifeng; Wei, Jiahua (Frontiers in Environmental Science, 2022)
For the droplets with different size distribution, reasonably selecting the frequency and period of acoustic waves are of great significance to acoustic agglomeration. To investigate critical responses of microdroplets under the action of low-frequency acoustic waves, laboratory experiments and numerical simulations of acoustic interference were conducted, and statistical test and theoretical analysis were carried out. A total of 1680 sets of experiments were performed, from which about 300,000 particle size samples were collected, with sound frequency of 30 ~ 280 Hz and the sound pressure level (SPL) of 70 ~ 130 dB. Droplet size distribution (DSD), equilibrium response time (ERT), the nodal plane in the air chamber and entrainment coefficient were analyzed. The critical SPL of acoustic agglomeration was 110 ± 15 dB based on average droplet size increment, and the variation of droplet size indicated that the ERT of acoustic intervention on microdroplets under the critical SPL was 44 ±12 s. In addition, lower sound frequencies corresponded to larger widths of droplet size with significant response (DSSR), which were jointly affected by sound pressure gradient (SPG), the entrainment coefficient and the droplet concentration. For microdroplets with unknown particle size distribution, acoustic intervention with variable frequencies is suggested for fog elimination and precipitation enhancement.